AB0359 Sarcopenia is Apparent in Patients with Rheumatoid Arthritis, Especially Those Treated with Biologics -Tomorrow Study-. (9th June 2015) - Inui, K.; Koike, T.; Tada, M.; Sugioka, Y.; Mamoto, K.; Okano, T.; Nakamura, H.
Abstract : Background: Patients with rheumatoid arthritis (RA) are reportedly at higher risk of developing metabolic syndrome because of the high concentration of tumor necrosis factor alpha in their sera. Sarcopenia is a component of metabolic syndrome; therefore, sarcopenia in patients with RA is thought to be related to RA disease activity. Objectives: We conducted a cross-sectional study to evaluate the relationship among skeletal muscle volume, disease activity, and insulin resistance, using the data in 2013 from TOMORROW study. Methods: In this study, we performed a sub-analysis of 2013 data in the TOMORROW study (UMIN: 000003876). This prospective cohort study examined several risk factors for osteoporosis and metabolic syndrome in patients with RA. The participants in the study comprised 202 patients with RA (109 patients receiving biological disease-modifying antirheumatic drugs [bDMARDs]) and 202 age- and sex-matched healthy volunteers (collected through mass media as controls). All participants completed a self-administered questionnaire on their general health status to provide baseline data. Laboratory data and anthropometric parameters were also collected. Body composition was determined by whole-body dual X-ray absorptiometry. A cross-sectional analysis of the data obtained from the cohort study in 2013 was performed in the present study. The relationship among sarcopenia, lipid metabolism, and insulin resistance was analyzed. Sarcopenia was defined as an appendicular skeletal muscle mass index (ASMI) of <5.46 kg/m 2 in females and <6.87 kg/m 2 in males. The ASMI was calculated as the patient's appendicular lean body mass divided by the square of the patient's height. Results: Sarcopenia was more apparent in patients with RA (6.14 kg/m 2 ) than in controls (6.55 kg/m 2 ) (p<0.001), especially in patients with RA treated with bDMARDs (tumor necrosis factor inhibitor, p=0.004; tocilizumab or abatacept, p<0.001) (Fig ). Insulin resistance as expressed by the homeostasis model assessment ratio (HOMA-R) was significantly higher in patients with RA treated with tocilizumab or abatacept (1.38) than in controls (0.93) (p=0.019). Regression correlation analysis among patients with RA revealed a strong and significant correlation between the ASMI and body mass index (R =0.553; p<0.0001) and between the HOMA-R and body mass index (R =0.304, p<0.0001). There was a significant but weak relationship between the ASMI and Disease Activity Score 28 (R = –0.196, p=0.0064) and between the ASMI and HOMA-R (R =0.145, p=0.0447). Conclusions: In this study, we showed that patients with greater RA disease activity who were receiving bDMARDs had lower muscle volume. Additionally, insulin resistance was significantly lower in patients with RA treated with bDMARDs other than tumor necrosis factor inhibitor. According to these results, patients with RA are more likely to have sarcopenia caused by metabolic syndrome. Because of the resultant frailty of these patients, sarcopenia should be taken into account at the time of starting prohibiting falling, subsequently expected fractures. Disclosure of Interest: K. Inui: None declared, T. Koike Grant/research support from: Takeda Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Chugai Pharmaceutical, Eisai, Abbott Japan, Teijin Pharma, Banyu Pharmaceutical and Ono Pharmaceutical, M. Tada: None declared, Y. Sugioka: None declared, K. Mamoto: None declared, T. Okano: None declared, H. Nakamura Grant/research support from: Chugai Pharmaceutical Co., Ltd., Astellas Pharma Inc., Nippon Zoki Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Takeda Pharmaceutical Co., Ltd., Hisamitsu Pharmaceutical Co., Inc., Ono Pharmaceutical Co., Ltd., Osteopharma Inc., Teijin Pharma Ltd., Asahi Kasei Pharma Co.